Activation of Gαq in Cardiomyocytes Increases Vps34 Activity and Stimulates Autophagy. Issue 4 (April 2017) - Liu, Shengnan; Jiang, Ya-Ping; Ballou, Lisa M.; Zong, Wei-Xing; Lin, Richard Z.
Abstract : Abstract: Receptors that activate the heterotrimeric G protein Gαq are thought to play a role in the development of heart failure. Dysregulation of autophagy occurs in some pathological cardiac conditions including heart failure, but whether Gαq is involved in this process is unknown. We used a cardiomyocyte-specific transgenic mouse model of inducible Gαq activation (termed Gαq Q209L) to address this question. After 7 days of Gαq activation, Gαq Q209L hearts contained more autophagic vacuoles than wild type hearts. Increased levels of proteins involved in autophagy, especially p62 and LC3-II, were also seen. LysoTracker staining and western blotting showed that the number and size of lysosomes and lysosomal protein levels were increased in Gαq Q209L hearts, indicating enhanced lysosomal degradation activity. Importantly, an autophagic flux assay measuring LC3-II turnover in isolated adult cardiomyocytes indicated that autophagic activity is enhanced in Gαq Q209L hearts. Gαq Q209L hearts exhibited elevated levels of the autophagy initiation complex, which contains the Class III phosphoinositide 3-kinase Vps34. As a consequence, Vps34 activity and phosphatidylinositol 3-phosphate levels were higher in Gαq Q209L hearts than wild type hearts, thus accounting for the higher abundance of autophagic vacuoles. These results indicate that an increase in autophagy is an early response to Gαq activation in the heart.